Diasporic subjectivity and ambivalent positionality in relation to orientalism in selected fiction by Eileen Chang - Qiao, Meng (2012)
Eileen Chang, who writes in both Chinese and English, has always been simply categorised as a Chinese writer. Researchers rarely approach her differently, such as a Chinese American writer or a diasporic writer, as if she had been living in China all the time and writing in Chinese only. This study, however, approaches Chang as a diasporic writer by analysing her selected fiction – Romances (1947), The Rice-Sprout Song (1955), Naked Earth (1956), The Rouge of the North (1967), The Fall of the Pagoda (2010), and The Book of Change (2010). The study explores how Chang positioned herself in relation to Orientalism during different periods of her writing, pointing out that although she subordinated herself to Orientalist discourse at times, she also tried to resist it in order to retain her agential subjectivity. The study also investigates the possible implications of diasporic writers’ positionality and critics’ evaluation on them through Chang’s diasporic experiences. A postcolonial perspective helps unravel the complexity of the construction of her diasporic subjectivity in the Orientalist discourse. Said’s analysis of Orientalism and Bhabha’s idea about the ambivalence of the construction of stereotypes provide the study with the theoretical basis. The major concept to be explored is diaspora, and Foucault’s understanding of discourse is adopted as the critical tool to unfold the analysis. The study demonstrates that Chang can be approached as a diasporic writer based on the analysis of the reason and route of her diasporic journey, her effort to merge into the host society, the indirect traces of her diasporic experiences in her writing, the marginalisation she suffered in the host land, and her nostalgia for the homeland. Treating her as a diasporic writer helps researchers to study her with more possibilities. Moreover, the analysis of her diasporic writing shows that critics can discover more by investigating how the liminal space of diasporic experiences contributes to diasporic writers’ articulation of their self-reflexivity instead of merely excluding them for inauthenticity, and that before labelling the diasporic writers as lf-Orientalising, critics need to take into consideration the ambivalent nature of the construction of stereotypes in Orientalist discourse. With regard to the positionality of the diasporic writers, this study points out that to maintain the agential subjectivity in the postcolonial era, the diasporic writers need to resist contributing to the epistemic production desired by the hegemonic power for its function.